Structural, elastic and optical properties of zinc borotellurite glass systems Co-doped with Ho₂O₃ and Ag₂O/Ag₂O NPs - Abdullahi, Usman (2019)
Series of zinc borotellurite glass doped with holmium oxide (Ho2O3), co-doped with holmium and silver oxide (Ag2O) and finally co-doped with holmium and silver oxide nanoparticles (Ag2O NPs) were successfully synthesized using the conventional melt quenching technique. The glass series were prepared using the chemical formulas of {((TeO2)0.7 (B2O3)0.3)0.7 (ZnO)0.3}1-x (Ho2O3)x (where x=0.005, 0.01, 0.02, 0.03, 0.04 molar fraction) and [{((TeO2)0.7 (B2O3)0.3)0.7 (ZnO)0.3}0.7 {(Ho2O3)0.3}]1-y (Ag2O/ Ag2O NPs)y (where y=0.01, 0.02, 0.03, 0.04, 0.05 molar fraction). XRD results confirmed the amorphous nature of the glass samples. The infrared spectra of the glass systems indicate the presence of TeO3, TeO4, BO3 and BO4 vibrational units in the various concentration of the series. The presence of silver nanoparticles was confirmed by the TEM images. The structural, elastic and optical properties of the glass systems were studied using various characterization techniques through densimetry, Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction spectroscopy, Ultra-Violet Visible Spectroscopy (UV-Vis) and Ultrasound measurement. For structural analysis physical parameters such as density, molar volume, oxygen molar volume, crystalline volume, excess volume, oxygen packing density (OPD) and dopant ionic concentration were studied. The density of Ho2O3 doped series increased from 4.5388 g/cm3 at 0.005 molar fraction to 4.9451 g/cm3 at 0.04 molar fraction while molar volume decreased from 26.1172 to 25.8159 cm3/mol accordingly. Similar trend of increase in density and decrease in molar volume were exhibited by the other two series. Generally, oxygen molar volume and excess volume show decreasing trend for all the three series as the concentration of the dopants were increased. While crystalline volume, OPD, and dopant ionic concentration increase with increase in dopants concentration. This behaviour generally increase the compactness and rigidity of the synthesized glass system. Substantial change was observed in the ultrasonic velocities (longitudinal and transverse velocities), elastic moduli (longitudinal modulus, Young modulus, bulk modulus and shear modulus), Poisson’s ratio, microhardness, softening temperature and Debye temperature which ascertained the changes that exist in the structure of the glass as a result of introduction of the dopants to the host structure. In all the glass series the elastic moduli show increasing trends, so also softening and Debye temperatures while microhardness follow decreasing trend as the dopant concentration decreased. Poisson’s ratio does not exceed maximum of 0.28 in its increasing trend for all the glass series. These behaviours illustrated by the generated elastic parameters are in favour of increase in the rigidity of the glass structure. The elastic moduli were also investigated theoretically using four models, Makishima- Mackenzie model, Rocherulle model, Bond compression model and Ring deformation model. It was established for this glass system that Ring deformation model gives excellent results that fit with experimental elastic moduli with more than 90% correlation coefficient in most of its values. Being a non-crystalline material, this glass system undergoes indirect transition with indirect optical band gap decreasing (Eopt) from 3.1169 eV at 0.01 molar fraction to 2.9702 eV at 0.04 molar fraction for Ho2O3 doped series. Similarly, Eopt decreased from 3.1899 to 2.3242 eV and from 2.7819 to 2.2093 eV for Ho2O3/Ag2O and Ho2O3/Ag2O NPs co-doped series respectively. The refractive indices show increasing trend as the dopants concentration increase for all the series. It was found that doping with Ho2O3/Ag2O NPs influenced the increase in refractive index most. The Urbach energy (ΔE) increases with increase in dopants concentration for all the three series. But the Ho2O3/Ag2O NPs doped series possessed highest Urbach energy of 0.4935 eV at 0.05 molar fraction. Molar electronic polarizability (αm) of this glass system follow increasing trend as the dopants concentration increase, with highest electronic polarizability of 11.1866 at 0.05 molar fraction realised for Ho2O3/Ag2O NPs doped series. Metallization criterion of this glass series decreases with increase of dopants concentration for all the series. The Ho2O3/Ag2O NPs doped series has lowest metallization criterion that falls between minimum of 0.3164 and maximum of 0.3591. The highest value of metallization criterion is 0.3865 for Ho2O3/Ag2O doped series. With this range of values for metallization criterion it is alarming that the synthesized glasses can serve as non-linear optical materials. The gain bandwidth obtained theoretically using McCumber theory confirmed that the synthesized glasses are potential candidate for photonics such as fiber lasers and amplifiers. Therefore, this research contributes towards addressing the pressing challenge of developing new materials for photonics.